Tinjauan Literatur tentang Manajemen Pembelajaran Berbasis Lingkungan dalam Bermain Guna Stimulasi Literasi Dini - Amalia, Wa Ode Sari; Nurlina, Nurlina; Usman, Usman (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
Environment-based learning in play is an approach that can improve the quality of early childhood literacy by optimizing children's interaction with the surrounding environment. However, the effectiveness of this approach is highly dependent on the learning management applied in the PAUD unit. This research aims to examine the concepts, implementation strategies, impacts, and challenges in the application of environment-based learning in playing to early literacy. The method used in this study is a literature review by analyzing various relevant scientific articles. The results of the study show that environment-based learning and play can improve children's literacy skills, engagement, and learning motivation. In addition, this approach also contributes to developing children's critical thinking and communication skills. However, the implementation of this strategy still faces various challenges, such as the readiness of educators, limited facilities and infrastructure, and lack of parental and community involvement. Therefore, training for educators, the development of flexible curriculums, and strengthening cooperation between schools, families, and communities are needed so that this approach can be applied optimally.